Analisis Efektivitas Kinerja Bidang Pembangunan Dan Pemberdayaan Masyarakat pada Kantor Camat Medan Timur Kota Medan - Muhammad Fauzi Pulungan; Nina Siti Salmaniah Siregar; Rudi Salam Sinaga (PERSPEKTIF, 2021)
So the formulation of the problem is how the effectiveness of the performance in the field of development and community empowerment at the East Medan District Head Office, Medan City? What are the obstacles in the field of development and community empowerment at the East Medan District Head Office, Medan City? The research method used in this research is qualitative analysis. Data collection is obtained from interviews, documentation, and observations. With the results of research on the productivity performance of employees in the field of Community Development and Empowerment, the East Medan Sub-district Office, Medan City has been effective. This can be seen in providing services in the form of the Implementation of Village Development Planning Deliberations for Preparation of Work Plans every year. Service quality in the field of Community Development and Empowerment, Medan Timur Sub-district Office, Medan City has not been effective. Responsiveness in the field of Community Development and Empowerment, Medan Timur Sub-district Office, Medan City is considered quite effective in setting goals and objectives to be achieved. Responsibility for Community Development and Empowerment, Medan Timur Sub-district Office, Medan City has been running effectively from the existence of priority programs. The accountability of activities carried out for the community and employees is very responsible and effective. The performance barrier in the field of Community Development and Empowerment is Human Resources. That education has a significant influence on employee performance. The suggestion from this research is to improve the quality by participating in training or coaching in order to increase the insight and motivation of personnel or human resources.